The first three terms of a sequence are given. Write your answer as a decimal or whole number. Round to the nearest thousandth (if necessary).

9, comma, 15, comma, 25, comma, point, point, .
9,15,25,...
Find the 10th term.
Find the 10th term..

1 answer

To find the 10th term of the sequence given the first three terms: 9, 15, and 25, we first need to determine the pattern of the sequence.

First, we can calculate the differences between consecutive terms:

  1. The difference between the second term (15) and the first term (9) is: \[ 15 - 9 = 6 \]

  2. The difference between the third term (25) and the second term (15) is: \[ 25 - 15 = 10 \]

So, the sequence of terms we have so far is:

  • 1st term: 9
  • 2nd term: 15
  • 3rd term: 25

Let's look at the differences:

  • The difference between the 1st and 2nd terms is 6.
  • The difference between the 2nd and 3rd terms is 10.

Now, let's find the differences of these differences (second differences):

  • The difference between the first difference (6) and the second difference (10): \[ 10 - 6 = 4 \]

Since the second difference is constant, this is a quadratic sequence. The general form of a quadratic sequence can be expressed as: \[ a_n = An^2 + Bn + C \]

Where:

  • \( A \) is half of the second difference.
  • \( B \) can be determined using the known terms.
  • \( C \) is the first term when \( n=1 \).

Since the second difference is \( 4 \): \[ A = \frac{4}{2} = 2 \]

Now let's write the sequence in terms of \( A \): \[ a_n = 2n^2 + Bn + C \]

We know:

  • \( a_1 = 9 \) => \( 2(1)^2 + B(1) + C = 9 \)
  • \( a_2 = 15 \) => \( 2(2)^2 + B(2) + C = 15 \)
  • \( a_3 = 25 \) => \( 2(3)^2 + B(3) + C = 25 \)

From \( a_1 \): \[ 2 + B + C = 9 \quad \text{(1)} \] From \( a_2 \): \[ 8 + 2B + C = 15 \quad \text{(2)} \] From \( a_3 \): \[ 18 + 3B + C = 25 \quad \text{(3)} \]

Solving equations (1), (2), and (3): From (1): \[ B + C = 7 \quad \text{(1)} \] From (2): \[ 2B + C = 7 \quad \text{(2)} \]

Subtract equation (1) from equation (2): \[ (2B + C) - (B + C) = 7 - 7 \] \[ B = 0 \]

Now plug \( B \) back into equation (1): \[ 0 + C = 7 \quad \Rightarrow \quad C = 7 \]

Then the expression for the nth term becomes: \[ a_n = 2n^2 + 0 \cdot n + 7 = 2n^2 + 7 \]

Now to find the 10th term: \[ a_{10} = 2(10)^2 + 7 = 2(100) + 7 = 200 + 7 = 207 \]

Thus, the 10th term of the sequence is: \[ \boxed{207} \]